Analysis of the Indonesian Consulate General Role in Hong Kong and the Implementation of Consular Functions - Ashari, Audila Andamita (Journal of ASEAN Dynamics and Beyond, 2022)
In 1951, Indonesia established the office of the Consultant General of the Republic of Indonesia in Hong Kong to braid economic cooperation in the region. As one of the world's trade centers, Hong Kong is an important trading partner for Indonesia. On the other side, as a part of China, Hong Kong does not have sufficient natural and human resources to meet its needs. There is a sense of interdependence, making their relationship last until today. This paper aims to determine Indonesian Consulate General role in Hong Kong and the implementation of consular unctions. with liberalism theory and descriptive literature research methods, the author concludes that the Indonesian Consulate General in Hong Kong organizes and participates in various trade economic activities. These efforts are said to be successful because they have had a positive impact on the development of the Indonesian economy.